Peer navigators to promote engagement of homeless African Americans with serious mental illness in primary care. (September 2017) - Corrigan, Patrick W.; Pickett, Susan; Schmidt, Annie; Stellon, Edward; Hantke, Erin; Kraus, Dana; Dubke, Rachel; ,
Abstract: Homeless African Americans with serious mental illness experience higher rates of morbidity and mortality than adults with severe mental illness alone. Peer navigators, individuals with similar lived experiences, may help these individuals navigate the healthcare system to improve healthcare utilization. This study examined whether the Peer Navigator Program (PNP) improved scheduling and achieving healthcare appointments compared to treatment as usual (TAU) over the course of 12 months, including three periods within that timeframe: engagement (first three months), impact (middle six months), and maintenance (final six months). Results indicated no change during the first three months of the study, a significantly greater improvement in scheduled and achieved appointments for PNP compared to TAU during the middle six months, and maintenance of appointment change improvements over the final three months of the study. This research suggests peer navigators may offer a promising solution to barriers in utilizing the healthcare system for people with severe mental illness, especially those who may be homeless or from minority racial groups.